2019
DOI: 10.5194/os-15-1191-2019
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Arctic Ocean surface salinities from the Soil Moisture and Ocean Salinity (SMOS) mission against a regional reanalysis and in situ data

Abstract: Abstract. Recently two gridded sea surface salinity (SSS) products that cover the Arctic Ocean have been derived from the European Space Agency (ESA)'s Soil Moisture and Ocean Salinity (SMOS) mission: one developed by the Barcelona Expert Centre (BEC) and the other developed by the Ocean Salinity Expertise Center of the Centre Aval de Traitement des Données SMOS at IFREMER (The French Research Institute for Exploitation of the Sea) (CEC). The uncertainties of these two SSS products are quantified during the pe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 38 publications
1
22
0
Order By: Relevance
“…Similarly, we found RMSD values of 1.5 and 3.3 for SMAP JPL and SMOS BEC matchups, while References [21] and [22] found values of 1.2 and 0.35. However, biases found in this study are between −0.6 and 0.5, which is comparable to 0.6 for SMOS in the Beaufort Sea found in Reference [23] and lower than 1, found in Reference [20] in subpolar seas.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Similarly, we found RMSD values of 1.5 and 3.3 for SMAP JPL and SMOS BEC matchups, while References [21] and [22] found values of 1.2 and 0.35. However, biases found in this study are between −0.6 and 0.5, which is comparable to 0.6 for SMOS in the Beaufort Sea found in Reference [23] and lower than 1, found in Reference [20] in subpolar seas.…”
Section: Discussionsupporting
confidence: 76%
“…They also found a standard deviation of the difference between the new SMOS SSS maps and Argo SSS that ranges from 0.25 to 0.35. Finally, a recent study from Reference [23] assessed the quality of only two SMOS SSS products in the Arctic Ocean from 2011 to 2013 by comparing these products to in-situ data. They found that in the Beaufort Sea, the SMOS product dedicated to the Arctic has the smallest bias (about 0.6) and the smallest RMSD (2.6).…”
Section: Introductionmentioning
confidence: 99%
“…These observations suggest complementarity between SMOS SSS and TOPAZ reanalysis products. This was already demonstrated by Xie et al (2019) for Arctic SSS produced at the Barcelona Expert center, but this is even more evident with this new product in very variable Arctic Seas (Appendix-H, Laptev Sea and Beaufort Sea).…”
Section: Conclusion and Discussionmentioning
confidence: 56%
“…After this date, they have been turned off in the northern high latitudes by emitting countries. Second, the sensitivity of L-band radiometric data to SSS gets lower with decreasing SST, hence the signal-to-noise ratio for individual retrievals decreases (Tang et al 2018;Olmedo et al 2018;Xie et al 2019). Furthermore, at high latitudes, SSS retrievals are more sensitive to errors in radiative transfer model components, e.g., uncertainties in sea surface roughness corrections, dielectric constant parameterization, high and variable wind speed more common at high latitude.…”
Section: Introductionmentioning
confidence: 99%